Program Penguatan Dan Pembetukan Karakter Sejak Dini di SDN Pradah Kalikendal 1 Melalui Kegiatan Pembinaan Kenakalan Remaja - Rizaldo Febriansyah; Rizkya Dwijayanti; Isrida Yul Arifiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Various forms of juvenile delinquency carried out by students have recently become widespread. This reality really makes parents, teachers, community leaders and even the government feel angry. To overcome this problem, the government finally established a policy of strengthening the character of education for the entire community, including the education sector. Because of the importance of enforcing educational character in schools, the author conducted research aimed at examining the role of the educational ecosystem in implementing strengthening character education for students in schools. The method used in this research is a qualitative method by conducting interviews and surveys at schools based on the results of the analysis. The results obtained are that the implementation of character values ​​by school principals, in the form of socializing school policies regarding character education, provides an example in implementing character values ​​to students, and so on, teachers, in the form of: teachers as the center of school civilization, providing opportunities for opinions equally to students, assessing and reporting learning outcomes fairly and transparently, especially those related to instilling character values, forming students' personalities, and so on , staff/educational personnel in the form of: neat appearance. Speaking politely, and so on, parents/community in the form of mediators (building networks) with other institutions or communities in the action of instilling character values ​​in schools, actively participating in school adiwiyata, holding training in schools, holding training in schools by inviting students. experts, and so on. With synergy in strengthening the character of education in schools, a conducive atmosphere will directly be created in the school environment.